Avaliação da combinação de diferentes métodos laboratoriais utilizados para diagnosticar e caracterizar Leptospira spp. a partir de amostras de sangue de pacientes com suspeita de leptospirose em Minas Gerais, Brasil, 2008 a 2014 - Marluce Aparecida Assuncao Oliveira (2016)
Introduction: Leptospirosis is an infectious and acute disease caused by leptospira spp. The disease has variable clinical features and is difficult to diagnose. Therefore, laboratory and epidemiological approaches are required to improve the detection of leptospirosis. Culture and serological methods have been used for laboratory diagnosis of leptospirosis from the end of the first week of the disease. These methods do not allow for an early diagnosis. Most cases in which patients progressing to death or not there is the opportunity of the second sample collection are not confirmed by immunological methods. Thus, our objective was to evaluate different laboratory methods for the diagnosis of leptospirosis, verify the occurrence of Leptospira spp. and genetic characterization the Leptospira spp. from the detected DNA samples from patients with suspected leptospirosis in Minas Gerais, Brazil, from 2008 to 2014. Methods: Samples of 78 patients were examined by the Enzyme Linked Immunosorbent Assay method (ELISA-IgM), Microscopic Agglutination Test (MAT), specific Polymerase Chain Reaction (PCR) in house using three different pairs of primers, and the Real Time PCR. The ELISA-IgM was performed with Panbio kits, following the manufacturers recommendations. The MAT and the culture were made under the National Reference Laboratory (Fiocruz/RJ) protocol. Two specific PCR were performed, one monoplex reaction (G1/G2 primers) and another duplex reaction (LipL41 F/R and flaâF/R primers). The Real Time PCR was optimized using the primers LipL32-45F/LipL32-286R and the probes LipL32-189PFAM and RNAseP3FAM. These primers specificity resulted in the amplification only from pathogenic serovars of Leptospira spp. The sensibility was equivalent to four genomic DNA copies. Products obtained by real-time PCR that showed Ct. greater than 36 and/or samples with more than 15-day disease course were sequenced by ABI platform 3730. The results were translated by BioEdit program and DNA/FASTA sequences were aligned using the BLAST database. Secondary data from MAT results were used to verify the Leptospira spp. seroprevalence from serum samples sent to LacenMG from 2008 to 2012. DNA molecular characterization from reference strains Leptospira spp. representing seven different genomic species was performed by the technique Low Stringency Single Specific Primer (LSSP-PCR). The profiles generated from 22 reference strains maintained in Lacen-MG were grouped by similarity of DNA using the BioNumerics software, version 7.1. Results: Our results support that the disease predominates in young people and adults with higher incidence in men. The methods separately used to leptospirosis diagnostics (MAT, ELISA-IgM, Culture, Monoplex PCR, Duplex PCR and Real Time PCR) presented a positivity of 16,7%; 20,5%; 1,3%; 9%; 13% and 10,3% respectively, when combined, they showed 33,5% positivity. The serologic methods presented a bigger positivity than the molecular methods, except when considered the disease evolution at the 0 4 days interval. The real-time PCR presented the best positivity results in this interval. The analysis of secondary data from MAT results showed higher frequency for the serovar Icterohaemorrhagiae. With two primers (flaâF1 and LipL41F) was possible differentiate 13 serovars and grouping by DNA similarity of strain isolated from patients which allowed us to consider the LSSP-PCR method a useful tool for identification of infectious serovars in cases of outbreaks and epidemics. Conclusion: Our results showed the importance of the studied methods execution in the appropriate disease evolution interval, what elevates the positivity of laboratory exams. We highlight the potential of real-time PCR when combined with other methods in order to diagnosis the human leptospirosis, in special, at the disease initial phase, the important moment in the disease clinical handling.